The Digital divide and its impact on Ecuadorian educational equity: Review from current pedagogy - Garcia Perdomo, Emilia Marisol; Lliguin Ochoa, Ronald Alfredo (Revista Minerva, 2025)
The post-pandemic (COVID-19) period highlighted inequalities in access to digital education, deepening the digital gap that already existed in contexts like ours, Guayaquil, Ecuador. This project aims, in addition to analyzing the influence of the digital divide on educational equity, to propose a solution that can be implemented in the educational field. We will focus on our Guayaquil context through a systematic bibliographic review of literature published between 2015 and 2024, based on academic data (Scielo, Redalyc, Dialnet, SpringerLink) and reports from international organizations (UNESCO, ECLAC). The results identify structural factors, such as limited technological infrastructure and insufficient teacher training, and sociocultural factors. Strategies based on connectivist, constructivist, and socio-critical approaches, aligned with the Ecuadorian national curriculum, are proposed to promote digital inclusion in education. These strategies would include disseminating and teaching the use of multiplatform and Web Based tools such as Google Classroom, Google Meet, WhatsApp, and YouTube, designed to be accessible. Promoting their use on basic devices and even with limited connections, with a view to improving access to online education with simple adjustments. Sharing their benefits for sustainable education and bridging gaps in resource-limited areas.
Keywords: Digital gap; educational equity; Guayaquil; inclusive education; information and communication technologies; critical pedagogy; Ecuadorian curriculum